2019
DOI: 10.1002/jlb.3a0318-108r
|View full text |Cite
|
Sign up to set email alerts
|

Iron alters macrophage polarization status and leads to steatohepatitis and fibrogenesis

Abstract: We have previously demonstrated that iron overload in hepatic reticuloendothelial system cells (RES) is associated with severe nonalcoholic steatohepatitis (NASH) and advanced fibrosis in patients with nonalcoholic fatty liver disease (NAFLD). Recruited myeloid‐derived macrophages have gained a pivotal position as drivers of NASH progression and fibrosis. In this study, we used bone marrow‐derived macrophages (BMDM) from C57Bl6 mice as surrogates for recruited macrophages and examined the effect of iron on mac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
76
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 135 publications
(86 citation statements)
references
References 37 publications
1
76
0
1
Order By: Relevance
“…In general, macrophages comprise two main phenotypes, classical M1 activation, and alternative M2 activation phenotypes, which regulate pro‐inflammatory and anti‐inflammatory responses, respectively 32 . An increase in hepatic M1 macrophages or a high M1/M2 ratio was observed in HF diet‐fed mice, triggering inflammatory processes and promoting the progression of NAFLD 33–35 . M2 activation of Kupffer cells by peroxisome proliferator‐activated receptor‐delta ameliorated obesity‐induced insulin resistance and hepatic steatosis 36 .…”
Section: Discussionmentioning
confidence: 99%
“…In general, macrophages comprise two main phenotypes, classical M1 activation, and alternative M2 activation phenotypes, which regulate pro‐inflammatory and anti‐inflammatory responses, respectively 32 . An increase in hepatic M1 macrophages or a high M1/M2 ratio was observed in HF diet‐fed mice, triggering inflammatory processes and promoting the progression of NAFLD 33–35 . M2 activation of Kupffer cells by peroxisome proliferator‐activated receptor‐delta ameliorated obesity‐induced insulin resistance and hepatic steatosis 36 .…”
Section: Discussionmentioning
confidence: 99%
“…Hepcidin binds to ferroportin and enhances its degradation. The accumulation of iron promotes "classically" activated macrophage polarization and production of proinflammatory cytokines that enhance the inflammatory response (157,158). Excessive iron accumulation in both KCs and hepatocytes is associated with NAFLD (152).…”
Section: Macrophages and Trace Metalsmentioning
confidence: 99%
“…Iron suppresses M1 polarization in Raw 264.7 macrophages, mouse bone marrow-derived macrophages and THP-1 monocyte-derived macrophages 57 59 and promotes M2 polarization in THP-1 monocyte-derived macrophages 59 , 60 . However, one study reported opposite results showing that iron increases M1 macrophage markers, but inhibits IL-4-induced M2 macrophage markers in mouse bone marrow-derived macrophages 61 . Iron decreases STAT1 phosphorylation in IFNγ-treated RAW 246.7 macrophages 57 , which is consistent with the iron-mediated inhibition of M1 macrophage polarization.…”
Section: Discussionmentioning
confidence: 97%